High cyclin D3 expression confers erlotinib resistance in aerodigestive tract cancer - Petty, W.; Voelzke, W.; Urbanic, J.; Varela, V.; Waller, L.; Swift, C.; Graham, Ross; Memoli, V.; Dragnev, K. (2011)
Background: Prior studies highlighted cyclin D1 as a key biomarker of response to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors. This study builds on prior work by examining the roles of cyclin D1, cyclin D3, and cyclin E in mediating erlotinib sensitivity or resistance. Methods: Expression plasmids for G1 cyclins were independently transfected into NIH 3T3 cells and effects on erlotinib sensitivity were examined. The expression profiles of G1 cyclins were compared in erlotinib-sensitive and erlotinib-resistant lung cancer cell lines. A549 and H358 cells were treated with erlotinib and changes in cyclin protein expression were assessed. Cyclin D3 immunohistochemical staining was measured in biopsy tissues obtained from patients before and after treatment with erlotinib. Erlotinib-sensitive lung cancer cells were transfected with cyclin D3 and changes in erlotinib sensitivity were examined. Results: Individual transfection of cyclin D1, cyclin D3, and cyclin E expression plasmids each significantly reduced erlotinib sensitivity in NIH-3T3 cells. The erlotinib-resistant A549 cell line expressed high basal levels of cyclin D3 mRNA and protein. Comparison of tumor biopsies obtained from patients before and after treatment with erlotinib indicated an increase in the percentage of cancer cells expressing cyclin D3 following treatment with erlotinib (P=.02). Transfection of cyclin D3 into an erlotinib-sensitive lung cancer cell line inhibited erlotinib-induced signaling changes and reduced the growth-suppressive effects of erlotinib. Conclusions: High expression of cyclin D3 confers resistance to erlotinib in vitro and in vivo. Cyclin D3 immunohistochemical staining warrants investigation as a biomarker for predicting erlotinib resistance. © 2011 Elsevier Ireland Ltd.